The Influence Of Online Attendance On The Work Discipline Of Civil Servants In The Communication And Informatics Office (DISKOMINFO) Of The Northern Nias District North Sumatra Province - Azpriman Putra; Fatolosa Hulu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of the implementation of online attendance on the work discipline of civil servants (PNS) at the Communication and Informatics Office (DISKOMINFO) of North Nias Regency, North Sumatra Province. Work discipline is one of the important aspects in assessing the quality of civil servant performance, which is directly related to the effectiveness of public services provided to the community. Along with technological developments, the manual attendance system previously used has now been replaced with a digital or online-based attendance system, such as the SIMPEG application implemented at DISKOMINFO. This research uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to DISKOMINFO employees. The independent variable studied in this research is the application of online attendance, while the dependent variable is employee work discipline. The data analysis technique used is statistical analysis to test the relationship between the two variables. The results showed that the implementation of online attendance has a significant positive effect on employee work discipline, with a t value of 4.524 (greater than t table 1.746) and a significance level of 0.000 (less than 0.05). In addition, regression analysis shows that the implementation of online attendance contributes 52% to improving employee work discipline. This research is expected to contribute to the development of a more efficient and effective attendance system in improving employee work discipline in the government. The application of online attendance has a positive and significant effect on the work discipline of civil servants.